POTENSI AIR KOLAM LELE BIOFLOK SEBAGAI PENGGANTI LARUTAN HIDROPONIK KOMERSIAL PADA BUDIDAYA TANAMAN SAWI - Suhardianto, Anang; Hartari, Ariyanti (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
The nutritional biofloc aquaponics system is a mutualism symbiosis between fish farming techniques and hydroponic plant cultivation. This system is an implementation of the spirit of urban farming and grow your own, which provides an answer to the limited land owned by urban communities as well as an effort to build food security for urban communities. This study aims to determine the effect of using biofloc catfish pond water and AB mix solution and the combination of the two for aquaponic cultivation of caisim, pakchoy, and kailan. Utilization of biofloc pond water and AB mix solution at a ratio of 1: 1 was able to provide the highest growth parameters in the form of plant height, number of leaves, and fresh weight for both caisim, pakchoy, and kailan plants. Biofloc catfish pond water can be used as a substitute for AB mix solution for aquaponic cultivation of caisim, pakchoy, and kailan. Keyword : biofloc catfish pond water, caisim, pakchoy, kailan